Exploring English Language Teachers' Experiences on Extensive Reading: An Interpretive Inquiry - Sharma , Janaki (Lumbini Journal of Language and Literature, 2024)
This study explores teachers' perspectives on extensive reading and it also highlights the challenges and support faced by English teachers in implementing Extensive Reading (ER) activities. It also explores whether extensive Reading could enhance students' motivation to read in English and foster positive attitudes towards reading in English. Novice and experienced teachers were involved and semi-structured interview was the main tool of data collection. The study involved two novice and two experienced teachers from private schools in Kathmandu. Semi-structured interviews were conducted with teachers. The findings show that while teachers recognized the benefits of ER and supported its implementation, challenges like tough books, lack of libraries, and lack of knowledge about the selection of level-appropriate books for students makes it hard to use ER. The study also suggests ER could be better way to teach reading in English language classroom because it makes reading fun and allows autonomy to select their reading resources. This study further attempts to contribute to the growth of future research in Extensive Reading in Nepal.